DEVELOPING THE TEACHING MATERIALS FOR WRITING SHORT STORIES BASED ON THE SAVI APPROACH (SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUAL) - Alfath Mellia Khairani Wijaya; Aswadi Jaya; Mega Prasrihamni (Esteem Journal of English Education Study Programme, 2023)
This development research aims to produce teaching materials that are valid, practical and have potential effects for fifth grade elementary school students. This research uses the type of development research (research and development). The development model in this study refers to the ADDIE model which consists of the analyze stage, the design stage, the development stage, the implementation stage and the evaluation stage. The collection of research data was obtained from validation sheets, student response questionnaires and tests. The results of the study of teaching materials for writing short stories based on the savi approach for fifth grade students based on a team expert validation questionnaire assessing in terms of media appearance, presentation of material and use of language as a whole obtained a percentage score of 95, 8% with a very valid category and suitable for use at the trial stage. The results of the One To One questionnaire obtained a percentage score of 91.6% in the very practical category and the results of the Small Group questionnaire obtained a percentage score of 93.4% in the very practical category. Then the results of student tests using teaching materials obtained a percentage of 84.60% in the very effective potential category. Based on the results developed by the researcher it was concluded that the Development of Short Story Writing Teaching Materials Based on the Savi Approach (Somatic, Auditory, Visualization, Intellectualy) for Grade V Elementary School Students meets the valid, practical, potential effect criteria and is appropriate for use in the process of learning Indonesian short story material.